O RELACIONAMENTO SOCIAL-ECONÔMICO-GERENCIAL INTERFIRMAS: O CASO DO CLUSTER DA INDÚSTRIA DO VESTUaRIO NO MUNICaPIO DE COLATINA (ES) - Garcia, Fernando Coutinho; Dadalto, Maria Cristina (Revista Economia Ensaios, 2008)
Resumo Três modelos de produção sobressaíram no decorrer do século XX: o modelo fordista, o modelo de coordenação e o modelo comunitário. A dinâmica de cada um desses modelos, por outro lado, está intrinsecamente relacionada à sociedade que os suscitou. Transpostos para o mundo das organizações, esses valores revelam-se por meio do relacionamento interfirmas. Neste artigo se analisa a dinâmica de relacionamento interfirmas no aglomerado da indústria do vestuário do município de Colatina, no Espírito Santo. A análise tem como principal referência a sistematização das principais características do modelo comunitário de produção dos Distritos Industriais (DIÂ´s) italianos. Abstract The 20th century was a period of deep social, economical, technological and organizational alterations. Underlying to the understanding of those transformations is the comprehension of the production model and the social regulation that permeate some society in its development process. Then, three production models stood out in elapsing of this century: the Ford model, the coordination model and the community model. The dynamics of each one of those models is inherently related to the society that raised them. So, we can relate the Ford model to the American consumer society, the coordination model to the Japanese hierarchical culture and the community model to the cooperation and reciprocity nets of the north of Italy. The evolution of each one of those models offers a certain answer to the organizational development, which also corresponds to specific periods in the relationship between economy and production. Paradoxically, in the current world, which demands fast answers, contacts seemingly superficial and flexibility, the Japanese and Italian production